The Selection Of Hemofiltration Regimen In Sepsis - A. N. Kudryavtsev; V. V. Kulabukhov; A. G. Chizhov (Общая реаниматология, 2016)
The results of a clinical trial using different high — volume hemofiltration regimens in surgical patients with sepsis is presented.Objective: improvement the clinical outcomes by inclusion the various regimens of a highvolume hemofiltration in the intensive therapy of patients with sepsis and septic shock.Materials and methods: The study enrolled 46 patients. Twentyfour patients underwent intermittent very high volume hemofiltration (IHVH) with a replacement volume of 100 ml/kg/h for 4 hours and 22 patients were provided by continuous highvolume hemofiltration (CHVH) with an ultrafiltration dose of 50 ml/kg/h for 48 hours.Results. In the IHVH group, 28day mortality was 29,2% that was significantly differed from that in the CHVH group (40,9%). The investigation revealed that a body mass index of more than 25 kg/m2 was a contraindications to IHVH.Conclusion. There were positive changes in the patient's condition associated with the stabilization of the circulatory system and the normalization of the oxygentransport function. These changes persisted during and after the IHVH and were similarly observed in the CHVH group. Patients with high body weight (more than 25 kg/m2) required special blood flow velocity regimen (320—350 ml per minute). Maintaining fraction of filtration for less than 25% and preventing thrombosis hemofilter during IHVH was crucial for effective treatment.